Systemic Sclerosis Presenting as Osteomyelitis of the Finger: Physicians Must Maintain a High Index of Suspicion for Systemic Sclerosis when Evaluating Patients with Fingertip Ulceration or Infection - Logan Van Poucke; Jared B Hinton; Holly C Heck; Benjamin E Heck; Bruce E Heck (Journal of Orthopaedic Case Reports)
Introduction: Osteomyelitis is a serious bone infection commonly caused by bacterial pathogens, with Staphylococcus aureus being the most prevalent. The condition poses significant challenges in patients with underlying autoimmune disorders such as scleroderma and Raynaud’s syndrome, where vascular dysfunction and immunosuppression heighten infection risks. This case report illustrates the complex interplay between these conditions and underscores the importance of early diagnosis and comprehensive management to prevent severe complications. Case Report: We present the case of a 79-year-old female with a history of Raynaud’s syndrome and suspected scleroderma who developed osteomyelitis of the left middle finger following a paronychial infection. The patient experienced persistent pain and swelling despite multiple debridement procedures. Physical examination revealed necrosis and gangrene of the affected finger, and magnetic resonance imaging confirmed osteomyelitis. Cultures identified Corynebacterium accolens, an uncommon pathogen in this context. The patient underwent surgical debridement, followed by antibiotic therapy and vasodilators. Her condition improved, with no signs of infection at follow-up. Conclusion: This case highlights the critical need for early and thorough assessment of infections in patients with autoimmune conditions such as scleroderma and Raynaud’s syndrome. The vascular dysfunction inherent in these diseases can exacerbate infections, leading to severe outcomes such as osteomyelitis. A multidisciplinary approach involving early surgical intervention and tailored medical management is essential to optimize patient outcomes.